2022
DOI: 10.1063/5.0093806
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic techniques for isolation, formation, and characterization of circulating tumor cells and clusters

Abstract: Circulating tumor cell (CTC) clusters that are shed from the primary tumor into the bloodstream are associated with a poor prognosis, elevated metastatic potential, higher proliferation rate, and distinct molecular features compared to single CTCs. Studying CTC clusters may give us information on the differences in the genetic profiles, somatic mutations, and epigenetic changes in circulating cells compared to the primary tumor and metastatic sites. Microfluidic systems offer the means of studying CTC clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 145 publications
0
23
0
Order By: Relevance
“…However, CTCs are difficult to detect and analyze, particularly due to their genetic and phenotypic heterogeneity and their scarcity in blood samples. Whole blood can contain less than 100 and sometimes even less than 10 clusters of CTCs per 10 7 leukocytes and 500 × 10 7 erythrocytes [ 66 , 67 ]. Despite being a rare event, CTCs offer great potential in liquid biopsy, which allows safe, inexpensive, and reproducible sampling as an alternative to invasive biopsy [ 68 ].…”
Section: Clinical Applications Of Ctc Enumeration and Ctc Subtypingmentioning
confidence: 99%
“…However, CTCs are difficult to detect and analyze, particularly due to their genetic and phenotypic heterogeneity and their scarcity in blood samples. Whole blood can contain less than 100 and sometimes even less than 10 clusters of CTCs per 10 7 leukocytes and 500 × 10 7 erythrocytes [ 66 , 67 ]. Despite being a rare event, CTCs offer great potential in liquid biopsy, which allows safe, inexpensive, and reproducible sampling as an alternative to invasive biopsy [ 68 ].…”
Section: Clinical Applications Of Ctc Enumeration and Ctc Subtypingmentioning
confidence: 99%
“…Microfluidic techniques have the possibility of investigating CTC clusters via the capability to proficiently separate these cells from the peripheral blood of patients in a liquid biopsy. Microfluidics can also be employed in in vitro experimental models of CTC clusters and allow their identification and study [ 59 , 60 , 61 , 62 ].…”
Section: Liquid Biopsy and Circulating Tumour Cellsmentioning
confidence: 99%
“…It has been found that clusters of circulating tumor cells (CTCs) have a greater propensity to cause metastases than single cells (3). Several studies have therefore included perfused tumor cell clusters, in addition to single CTCs, into microfluidic vasculature to mimic circulating tumor cluster transportation in vivo (59,90).…”
Section: Extravasation Of Tumor Cell Clusters and Other Recent Studiesmentioning
confidence: 99%
“…Cancer metastasis often begins when tumor cells undergo an epithelial-to-mesenchymal transition (EMT), in which they acquire higher motility and invasiveness and break away from the primary tumor (2). Then, these tumor cells invade surrounding tissues, intravasate to the nearby microvasculature as either single cells or cell clusters, and become circulating tumor cells (CTCs), often aggregating with platelets or monocytes, enabling them to withstand fluid shear stress or anoikis (3) and avoid attack by circulating NK cells. Surviving CTCs can then adhere to the endothelium and extravasate into the distant secondary organ and subsequently progress into metastatic tumors (Figure 1).…”
Section: Introductionmentioning
confidence: 99%